PENGEMBANGAN MODUL PEMBELAJARAN INQUIRY DRILL MATERI PERSAMAAN AKUNTANSI MAS AWALUDDIN KUBU RAYA - Qomariyah, Siti; Mering, Aloysius; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractSome problems in understanding accounting fundamental equation most of them caused by accounting fundamental equation material was memorizing and accounting, so that those were difficult to understand by student, in this case learning media as inquiry drill was needed to improve learning proses and learning output. This study was aimed to produce learning module program of inquiry drill in economic learning accounting fundamental equation material. The research and development procedures were taken from Borg and Gall and module design used ADDIE model, the subjects of this study were class elevent students which containt28 students. The anvanced of developing of module design analys, design, development, implementation and evaluation. The instruments collect data were gotten from expert validation inquiry, observation, interview, student’s respond inquiry and dokumentation. Then the reseacher did analys the data on the expert validation inquiry output, observation, interview and student’s respond inquiry.The result of the study showed that inquiry drill learning module could give positive effect of the learning of accounting fundamental equation material; these could be seen from the result of pre-test before learning proses used inquiry drill learning module, the average score was 52,42 and the percentage 7,14%, and the post-test after using inquiry drill learning module, the average score was 87,62 and the percentage 96,42%, so that, from this presentation showed that students had increase in learning proses of accounting fundamental equation material used inquiry drill learning module. Besides that, the increase of the students learning proses could be seen from two couple sample showed that t value < t table (10,42>2,048), means that there was increasing of the learning proses by using inquiry drill learning module in economic learning accounting fundamental equation material. The result above, inquiry drill learning module could help student in learning fundamental equation material of accounting was easier. Key word: development, inquiry drill learning module, fundamental equation accounting